(untitled) (Mongolian Journal of Agricultural Sciences, 2021)
Coated seeds will be used to protect crops from various pests and diseases, and increase the intensity of growth and germination. To gaining the size and weight of seeds is also useful to equalize the distance between crops by its agro-technical requirement at the sowing time. Many methods can be used for the seed coating process, but the general principles are same. One or more different substances can be applied to seed surface with numerous layers. Fodders, protectors and fillers can be included for those substances, which are not only used to sizing of the seeds, but also used for making seeds with convenient shape. We determined the density of coated seeds was 660 kg / m3, the coefficient of external friction was 0.47, the coefficient of internal friction was 0.56, and the average value of coating load was 33N, which meets the agro-technical requirements for sowing. Comparative number of coated rapeseed (by seed meter) to number of non-coated rapeseed for falling at one square meter were decreased by 1.4-3.6 times. It shows the problem of 2.1-2.6 times more seeds were falling than the basic norm when rapeseed is sown has been solved, and due to the increase of seed weight the seeds evenly falling through the seed tube and sitting evenly at the bottom of the drill-harrow has been improved. Рапсийн бүрсэн үрийн технологийн ба агро техникийн үзүүлэлтүүдийг судалсан дүн Тус өгүүлэлд бүрсэн үрийн физик механик шинж болон агро техникийн шаардлагыг хэрхэн хангаж байгааг туршилтаар тодорхойлсон үр дүнг харууллаа. Туршилтын үр дүнд бүрсэн үрийн эзлэхүүн жин 660 кг/м3, бяцралын хүч нь 33Н, катушкан үрлэх аппаратаар үрлэж бүрсэн рапсын үрийг бүрээгүй үртэй харьцуулахад 1м.кв-т талбайд унах үрийн тоог 1.4-3.6 дахин багасгаж байна. Түлхүүр үг: үрэлтийн илтгэлцүүр, эзлэхүүн жин, нягт, бяцрал, жин